2009
DOI: 10.1021/jp9022986
|View full text |Cite
|
Sign up to set email alerts
|

Influence of in Vitro Degradation of a Biodegradable Nanocomposite on Its Shape Memory Effect

Abstract: Preparation and in vitro degradation of shape memory nanocomposites consisting of cross-linked poly(εcaprolactone) (c-PCL) and Fe 3 O 4 nanoparticles were investigated in this study. The degradation behaviors were evaluated from the decrease of mechanical property, weight, and molecular weight of polymer, the change of pH value of phosphate-buffered saline (PBS), and morphological changes in composites. The results from gel fraction and molecular weight analysis indicated some damages were brought to chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 33 publications
0
27
1
Order By: Relevance
“…Note that the SM characteristics are markedly reduced with the degradation time. This was shown on example of PCL-based systems degraded in vitro [69]. T trans adjustment to body temperature and controlled biodegradability will remain preferred research topics further on [70].…”
Section: Discussionmentioning
confidence: 98%
“…Note that the SM characteristics are markedly reduced with the degradation time. This was shown on example of PCL-based systems degraded in vitro [69]. T trans adjustment to body temperature and controlled biodegradability will remain preferred research topics further on [70].…”
Section: Discussionmentioning
confidence: 98%
“…The lactic acid resulting from the degradation of PLLA was neutralized effectively by surface modified magnesia[166]. Thus, Fe 3 O 4 can facilitate the infiltration of degradation medium into composite and promote its degradation[169]. The rate of enzymatic degradation of P(3HB-co-4HB) has enhanced significantly in nanocomposites of poly(3- hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)]/silica.…”
mentioning
confidence: 99%
“…To demonstrate this, Yu et al showed the decreased recovery ratios of a magnetite-filled, crosslinked PCL network. After up to 14 weeks in phosphate-buffered saline, the total recovery time and gel fraction of the networks significantly decreased, showing a notable relationship between increasing magnetite filler ratio and decreased mechanical properties [105].…”
Section: Enhancing Biocompatibilitymentioning
confidence: 98%